2019
DOI: 10.1093/ecco-jcc/jjz040
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Tolerability, and Safety of Low-Volume Bowel Preparations for Patients with Inflammatory Bowel Diseases: The French Multicentre CLEAN Study

Abstract: Background Standard high-volume polyethylene glycol [PEG] bowel preparations [PEG-4L] are recommended for patients with inflammatory bowel disease [IBD] undergoing colonoscopy. However, low-volume preparations [≤2 L of active volume] are often used in clinical practice. The aim of this study was to evaluate the efficacy, tolerability, and safety of the various bowel preparations for patients with IBD, including low-volume preparations. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“… 18 , 19 Moreover, in a multicenter observational study conducted in France on the best colonoscopy preparation agent for inflammatory bowel disease, both agents PICOPREP and PEG‐2L were equally safe and were reported to have significantly better efficacy and patient acceptability than PEG‐4L. 20 In this study, UC was observed in 33 patients (61.1%), a well‐known cause of unknown chronic diseases. Therefore, a stable remission period should be considered for long‐term treatment.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“… 18 , 19 Moreover, in a multicenter observational study conducted in France on the best colonoscopy preparation agent for inflammatory bowel disease, both agents PICOPREP and PEG‐2L were equally safe and were reported to have significantly better efficacy and patient acceptability than PEG‐4L. 20 In this study, UC was observed in 33 patients (61.1%), a well‐known cause of unknown chronic diseases. Therefore, a stable remission period should be considered for long‐term treatment.…”
Section: Discussionmentioning
confidence: 65%
“…According to the consensus statement and guidelines compiled by the American and European academic societies, the effectiveness of PICOPREP is evaluated to be almost the same as that of conventional PEG 18,19 . Moreover, in a multicenter observational study conducted in France on the best colonoscopy preparation agent for inflammatory bowel disease, both agents PICOPREP and PEG‐2L were equally safe and were reported to have significantly better efficacy and patient acceptability than PEG‐4L 20 . In this study, UC was observed in 33 patients (61.1%), a well‐known cause of unknown chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the quality of bowel preparation requirements will be higher. More recently, consistent literature data confirmed that high-quality bowel preparation is a key factor in endoscopy [ 29 , 30 ]. In this study, the satisfaction rate of adequate bowel preparation in the 1.5 L + 0.75 L group was higher than in the 0.75 L + 1.5 L group, and we analyzed the reasons and found in clinical practice, although the patients in both groups completed bowel cleansing according to the corresponding bowel preparation regimen, and determined that their last stool was clear water, the patients in the 1.5 L + 0.75 L group tolerated higher, and the proportion of vomiting was less than that of the 0.75 L + 1.5 L group, so the bowel cleansing of the patients in the 1.5 L + 0.75 L group was better than that of the 0.75 L + 1.5 L group.…”
Section: Discussionmentioning
confidence: 75%
“…Only 2 of those studies have been performed in recent years (2015 and 2017) (15) (16): they were both randomized trials and compared large-volume PEG (4L-PEG) with 2L-PEG plus ascorbic acid/bisacodyl; however, they only admitted patients with inactive UC. The 2019 French Multicenter CLEAN study (17) is the largest and most recent study regarding this matter. It found no differences between 4L-PEG vs 2L-PEG and SP regarding colon cleansing, in both CD and UC; and though prospective, its design was observational.…”
Section: Discussionmentioning
confidence: 99%
“…Trials by Manes et al (15) and Kim et al (16) found no differences regarding colon cleansing between 4L-PEG and 2L-PEG; however, differences in design (i.e., use of high-volume preparations and excluding patients with CD) hindered us from comparing our data. The CLEAN trial (17) found that 2L-PEG and SP were signi cantly superior (p = 0.0021 and 0.0020, respectively) to 4L-PEG for colon cleansing in all subtypes of IBD. The mean BBPS in the CLEAN study was 7.6 for 2L-PEG and 7.7 for SP; our results numerically favored SP (7.35 for 2L-PEG and 8.09 for SP) but did not reach statistical signi cance.…”
Section: Discussionmentioning
confidence: 99%